Ungkur-Ungkur sebagai Kearifan Lokal dalam Tradisi Selamatan Kematian di Dusun Ngreco, Desa Rembang, Kediri - Syaifudin, Syaifudin; Nabiel, Muhammad; Framono, Muhamad Dwi (Proceedings of Annual Conference for Muslim Scholars, 2025)
The Ungkur - Ungkur tradition represents a Javanese cultural practice closely related to death rituals, embodying profound social and spiritual values. This study aims to explore the symbolic meanings and social functions of the Ungkur - Ungkur tradition as a representation of local wisdom that contributes to the development of social tolerance and communal harmony within an Islamic perspective. Employing an Islamic ethnographic approach, data were collected through participatory observation, in - depth interviews, and ritual documentation. The findings reveal that Ungkur-Ungkur is not merely a customary ritual but also a social space that integrates cultural values with Islamic teachings, particularly in the context of human solidarity and mutual respect. Practices such as collective prayer, cooperation, and honoring ancestors serve as media for internalizing Islamic values of brotherhood (ukhuwah) and compassion. Therefore, Ungkur - Ungkur functions as both a means of cultural preservation and a medium of social reconciliation that strengthens community cohesion.